(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study examined undergraduates’ level of study as determinant of perception, knowledge and attitude towards global warming among undergraduates in Ekiti State, Nigeria. The descriptive research survey design was adopted in this study. The population consisted of all undergraduates in all the Universities in Ekiti State. The sample for this study consisted of 600 undergraduates which were selected from the three universities in Ekiti State. The sample was selected through multistage sampling procedure. A questionnaire designed by the researcher tagged “Global Warming Questionnaire (GWQ)” was used to collect relevant data for the study. The face and content validity of the instrument was done by specialists in Social Studies and Tests and Measurement experts. The reliability of the instrument was ensured through test re-test method of reliability. The scores of the two tests were correlated using Pearson Product Moment Correlation Coefficient Analysis. The correlation coefficient of 0.82 was obtained which was good enough to make the instrument reliable. The research hypotheses generated were tested using inferential statistics. The study revealed that there was no significant difference in knowledge and perception of global warming among undergraduates based on level but there was significant difference between attitudes of undergraduates towards global warming based on level, It was recommended that curriculum planners and other education stakeholders should see to regular review of tertiary institutions curriculum by updating new developments on global warming into the curriculum for undergraduates to familiarize themselves with latest information concerning global warming.